Kualitas Madu Lebah Apis dorsata Desa Semalah Kabupaten Kapuas Hulu Kalimantan Barat - Hilda Aqua Kusuma Wardhani; Desi Ratnasari; Siti Nur Kotimah (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2022)
Honey is a sweet natural liquid produced by honey bees from the nectar of plant flowers (floral nectar), other parts of plants (extra floral nectar), or insect excretions. One of the largest honey-producing areas in Indonesia is located in Semalah Village, Kapuas Hulu Regency, West Kalimantan. This study aims to analyze the quality of Apis dorsata honey bees produced in Semalah Village, Kapuas Hulu Regency. This research was conducted from January to March 2022. The sampling of tikung and lalau honey from Apis dorsata bees was taken by purposive sampling technique. The sample then were analyzed for physical quality (smell and taste) and chemical (water content, acidity, HMF levels, glucose, sucrose, and diastase enzyme activity) at the Food Technology Laboratory, Faculty of Engineering, Pasundan University, Bandung. The data was then analyzed descriptively and adjusted to the Indonesian National Standard (SNI) Number 8664:2018 regarding honey. Based on the results of the organleptic test, the two samples of tikung honey and lalau honey of Apis dorsata bees from Semalah Village, Kapuas Hulu Regency had honey characteristics by SNI number 8664 of 2018, and based on the results of the chemical test of honey, all test parameters (acidity, hydroxymethylfurfural levels, glucose, sucrose, and diastase enzyme activity) in accordance with SNI number 8664 of 2018 concerning honey, except for the water content parameter. The water content in samples of tikung honey and lalau honey of Apis dorsata bees from Semalah village, Kapuas Hulu Regency did not meet the standards set by SNI number 8664 of 2018. Keywords: Quality, Honey, Apis dorsata, Semalah Village  Abstrak  Madu adalah cairan alami dengan rasa manis yang dihasilkan oleh lebah madu dari nektar bunga tanaman (floral nektar), bagian lain dari tanaman (ekstra floral nektar) atau ekskresi serangga. Kalimantan Barat khususnya Kabupaten Kapuas Hulu merupakan salah satu daerah penghasil madu terbesar di Indonesia. Penelitian ini bertujuan untuk menganalisis kualitas madu lebah Apis dorsata yang dihasilkan di Desa Semalah Kabupaten Kapuas Hulu. Penelitian ini dilaksanakan pada bulan Januari sampai Maret 2022. Pengambilan sampel madu tikung dan lalau lebah Apis dorsata dilakukan dengan teknik purposive sampling. Sampel selanjutnya akan dianalisis kualitas fisik (bau dan rasa) dan kimia (kadar air, kadar HMF, keasaman, glukosa, sukrosa, dan aktivitas enzim diastase) di Laboratorium Teknologi Pangan Fakultas Teknik Universitas Pasundan Bandung. Data kemudian dianalisis secara deskriptif dan disesuaikan dengan Standar Nasional Indonesia (SNI) Nomor 8664:2018 tentang madu. Berdasarkan hasil uji organleptik, kedua sampel madu tikung dan madu lalau lebah Apis dorsata asal Desa Semalah Kabupaten Kapuas Hulu memiliki karakter madu sesuai dengan SNI nomor 8664 tahun 2018 dan berdasarkan hasil uji kimia madu, seluruh paramater uji (keasaman, kadar hidroksimetilfurfural, glukosa, sukrosa, dan aktivitas enzim diastase) sesuai dengan SNI nomor 8664 tahun 2018 tentang madu, kecuali pada parameter kadar air. Kadar air pada sampel madu tikung dan madu lalau lebah Apis dorsata asal desa Semalah Kabupaten Kapuas Hulu tidak memenuhi standar yang sudah ditetapkan oleh SNI nomor 8664 tahun 2018. Kata kunci: Kualitas, Madu, Apis dorsata, Desa Semalah